Positive solutions to a class of fractional differential equations with boundary value conditions - Bouderbala, Khaoula; Boukehila, Ahcene, Directeur de thèse (Laghouat : Université Amar Telidji - Département de mathématiques, 2024)
The objective of this master’s memory is to study positive solutions for fractional differential equations. In the second chapter, the considered problem is subject to integral boundary value conditions (IBVC), and the third one aims to study fractional differential equations (FDEs) with Hadamard derivatives We provide some examples for each problem.